2005
DOI: 10.1002/ar.a.20229
|View full text |Cite
|
Sign up to set email alerts
|

Tumor necrosis factor‐α‐induced changes in insulin‐producing β‐cells

Abstract: The migration of macrophages and lymphocytes that produce cytokines such as tumor necrosis factor-␣ (TNF-␣) causes ␤-cell death, leading to type 1 diabetes. Similarly, in type 2 diabetes, the adipocyte-derived cytokines including TNF-␣ are elevated in the circulation, causing inflammation and insulin resistance. Thus, the studies described in this article using TNF-␣ are relevant to furthering our understanding of the pathogenesis of diabetes mellitus. We used RINr1046-38 (RIN) insulin-producing ␤-cells, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 70 publications
0
19
0
1
Order By: Relevance
“…Grunnet et al 2009 demonstrated that the proinflammatory cytokines IL-1β, IFN-γ, and TNF-α led to a calcium-activated, calcineurin-dependent dephosphorylation of the pro-apoptotic protein Bad, which caused beta-cells to undergo apoptosis [164]. Parkash et al 2005 demonstrated that TNF-α-treated RIN beta-cells expressed significantly less calbindin-D and a greater [Ca 2+ ] i response to increasing concentrations of ionomycin when compared to controls [168]. Further, TNF-α induced localization of the proapoptotic protein, Bax, to the perinuclear regions of RIN cells that contain the highest density of mitochondria, implying a calcium-dependent link between TNF-α and activation of the mitochondrial apoptotic pathway [168].…”
Section: Mitochondrial Calcium and Cytokine Actionmentioning
confidence: 99%
See 1 more Smart Citation
“…Grunnet et al 2009 demonstrated that the proinflammatory cytokines IL-1β, IFN-γ, and TNF-α led to a calcium-activated, calcineurin-dependent dephosphorylation of the pro-apoptotic protein Bad, which caused beta-cells to undergo apoptosis [164]. Parkash et al 2005 demonstrated that TNF-α-treated RIN beta-cells expressed significantly less calbindin-D and a greater [Ca 2+ ] i response to increasing concentrations of ionomycin when compared to controls [168]. Further, TNF-α induced localization of the proapoptotic protein, Bax, to the perinuclear regions of RIN cells that contain the highest density of mitochondria, implying a calcium-dependent link between TNF-α and activation of the mitochondrial apoptotic pathway [168].…”
Section: Mitochondrial Calcium and Cytokine Actionmentioning
confidence: 99%
“…Parkash et al 2005 demonstrated that TNF-α-treated RIN beta-cells expressed significantly less calbindin-D and a greater [Ca 2+ ] i response to increasing concentrations of ionomycin when compared to controls [168]. Further, TNF-α induced localization of the proapoptotic protein, Bax, to the perinuclear regions of RIN cells that contain the highest density of mitochondria, implying a calcium-dependent link between TNF-α and activation of the mitochondrial apoptotic pathway [168]. The uncoupling protein (UCP2) is another established effector of mitochondrial-mediated beta-cell death in several models of immune-mediated diabetes [169-171], and UCP2 is also known to regulate mitochondrial calcium sequestration [172].…”
Section: Mitochondrial Calcium and Cytokine Actionmentioning
confidence: 99%
“…The important cytokine TNF-α which has a pathogenetic role in β-cells apoptotic death [39] and is recognized as a contributing factor in insulin resistance and dyslipidemia [40] was not downregulated in all of the experimental groups (the tendency towards the reduction was seen in the group receiving metformin, Table 1). Still the negative correlation between insulinemia and TNF-α appeared against the background of the tincture.…”
Section: Figure5 Photomicrographs Of the Liver Of The Alloxan-inducementioning
confidence: 95%
“…However, consistent with genetic studies on combined knockdown of CaR and EP2, treatment with the anti-CaR and anti-EP2 combinations as well as AH6809 and npS 2143 combination should reduce the rate of cell proliferation, reduce the trans-endothelial migration and increase the rate of apoptosis much more significantly. The rate of cell replication can be measured by the incorporation of 5-bromodeoxyuridine as defined previously (28,29). In order to study changes in the rate of apoptosis, cleaved caspase-3 can be quantified by using fluorescence microscopy in combination with monoclonal antibody conjugated with fluorescein-isothiocyanate (FITC) that specifically recognizes the active form of caspase-3 in cells.…”
Section: Test Of Hypothesismentioning
confidence: 99%